Educational Revolution through the Application of AI in the Digital Era - Agus Nursalim; Loso Judijanto; Asfahani Asfahani (Journal of Artificial Intelligence and Development, 2022)
The rapid advancement of artificial intelligence (AI) technology has sparked an educational revolution, transforming traditional teaching methodologies and learning approaches in the digital era. This study aims to investigate the impact of AI application in education, focusing on personalized learning experiences, student engagement, critical thinking development, and data-driven decision-making. The research utilizes a Systematic Literature Review (SLR) methodology to gather and analyze relevant empirical evidence and theoretical frameworks. The results highlight significant improvements in personalized learning, increased student engagement, enhanced critical thinking skills, and improved data-driven decision-making processes facilitated by AI technology. The findings contribute to a deeper understanding of the educational revolution driven by AI in the digital era and underscore the importance of responsible AI integration for fostering inclusive, innovative, and effective education systems.